Implementasi Sistem Pemerintah Berbasis Elektronik Dalam Mewujudkan Smart City Di Dinas Kominfos Denpasar Bali - Agus Bahrudin; Christine Diah Wahyuningsih (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The smart city action plan for the city of Denpasar Bali includes: 1) human resources 2) nfrastructure, 3) applications, and 4) smart city literacy. Meanwhile, in building a smart city there are six pillars, namely smart governance, smart society, smart living, smart economy, smart environment, and smart branding. In 2020 Denpasar City ranks 1st Smart City with Surakarta in the framework of the movement program towards 100 Smart Cities Indonesia.The 2021 Electronic-Based Government System Index is 3.19 which is in the good category and is in the Top 5 RKCI that year. The Denpasar Bali City Communication, Information and Statistics Service (Kominfos) has taken several steps to implement e-government in realizing a smart city. Some of these steps include building an e-gov portal, increasing accessibility, using the right technology, establishing partnerships with the private sector, developing mobile applications. By implementing e-gov and developing a smart city, the Denpasar-Bali City Communication and Informatics Agency is able to improve the quality of public services, facilitate public access to information and public services, and increase the efficiency and effectiveness of the performance of the Denpasar city government.